The Influence of Researchers Upon Glacial Stratigraphy - Dreimanis, Aleksis (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1982)
Abstracts In order to illustrate how glacialstratigraphy may become influenced bythe subjectivity of researchers, the grainsize composition of till will be discussedas an example. Most particle size data donot refer to the entire till, but mainly to itsmatrix, plus smaller clasts. Though thegranulomere data, even if just referringto till matrix, are considered to be reliableand objective, various amounts of subjec-tivity enter the analytic results during thesampling, pretreatment, analyses andstatistical evaluation of data. The subsequent interpretation involveseven more subjectivity. This will beillustrated by using tills of SouthwesternOntario and Denmark as examples. Whilecolour and texture of till once used to bethe main criteria for differentiation andcorrelation of tills, more complex multiplecriteria are applied now. During the last15 years a score of genetic varieties oftills have become recognized, each ofthem playing its role in stratigraphieinterpretation. Now more attention thanbefore is paid to glaciotectonicdeformations and fabric in decipheringstratigraphy of glaciogenic sequences. Quaternary glacial deposits cover mostof Canada. If their stratigraphy has beenproperly deciphered, the extraction ofQuaternary economic deposits and theplanning of major construction projectsmay be done rationally. The knowledgeof glacial stratigraphy is useful also inhydrogeology and in planning waste dis-posal. In the search for bedrock ore depo-sits by indicator tracing, anunderstanding of Quaternary glacialstratigraphy is essential in areas withmore than one layer of glaciogenicdeposits over bedrock.